PERILAKU RESOURCEFULLNESS DAN PRESTASI AKADEMIK MAHASISWA DITINJAU DARI STRATEGI EXPERIENTIAL LEARNING - Eva Latipah (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2014)
This study aimed to examine the effect on behavior resourcefullness learning strategies. The next test was conducted to determine the relationship between behavior and academic achievement resourcefullness general psychology.There are three instruments used in this study, namely modules experiential learning strategies, scale resourcefullness, and learning achievement of learning psychology. Module experiential learning strategy is a guideline to implement better teaching strategies EL in general psychology. Resourcefullness Scale is a tool to find out resourcefullness research subjects. To measure the achievement of general psychology using existing documents, ie the final value of a general psychology course, which is accessed from SIA Program (Academic Information System) UIN Sunan Kalijaga.Subjects in this study were all students of men and women who are taking courses in general psychology, class of 2011/2012 academic year (3rd semester of college is done). The number of subjects in this study were eighty-three (83) students, in which 42 people (class A) as the experimental group, and 41 people (class B) as a control group.Analysis of the data according to the hypothesis that will be formulated using different test techniques (t-test) and test product moment with the help of a computer program SPSS version 16. To examine why and how a change (as the effect of the treatment, will be done using interview techniques.